Evaluation of single particle drying characteristics using drying models and curve fitting - Celen, Pinar; Erdem, Hasan H.; Pusat, Saban (TAYLOR & FRANCIS INC, 2022)
In this study, Turkish lignite dried with hot air and superheated steam was experimentally investigated. Drying experiments were carried out at 120 degrees C drying temperature and atmospheric pressure. Mass, center and surface temperature changes of lignite having a diameter of 30 mm were continuously measured. Hot air and superheated steam drying methods were compared, and it was found that, because of condensation in the initial stage of superheated steam, the moisture content of the lignite sample temporarily increased. On the contrary, the moisture content of the lignite sample dramatically reduced on drying with hot air. Six different thin-layer models describing the drying kinetics of lignite were fitted to the experimental data, with the Pusat model giving the best predictions with superheated steam drying and the Midilli model giving the best predictions with hot air drying of a single particle.
Keywords: Lignite; drying; steam drying; air drying; COAL MOISTURE-CONTENT; KINETICS; MICROWAVE; BEHAVIOR; Energy & Fuels; Mining & Mineral Processing